Water cup
By forming a transparent modified ceramic coating on the inner surface of the water cup, combined with inorganic polysilazane material and silane material, the problem of easy scaling of the glass water cup is solved, achieving easy cleaning and antibacterial effects.
Patent Information
- Application Number
- CN202111242878.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-10-25
AI Technical Summary
Existing glass cups are prone to forming dirt that is difficult to clean after use, mainly tea scale and scale caused by organic, inorganic and microbial metabolites.
A transparent modified ceramic coating with antibacterial material added on the inner surface of the water cup is formed. By combining the inorganic polysilazane material and the silane material, a nano-silia base layer and a ceramic non-stick layer are formed to increase antibacterial properties.
It is achieved that the water cup is not easy to scale during use, or the scale can be easily removed by rinsing water or wiped with cloth, and has good antibacterial effects to prevent the reproduction of bacteria and fungi.
Smart Images

Figure CN116023042B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cups, and in particular to a water cup. Background Art
[0002] After long-term use, the micropores on the inner surface of existing glass water cups will absorb dirt and are difficult to clean, affecting the user experience. Among them, the sources of dirt are mainly three types: first, the tea scale formed by the organic and inorganic substances dissolved after brewing tea and deposited on the glass surface; second, the scale formed by the precipitation of calcium and magnesium ions in water with high hardness and deposited on the glass surface; third, the metabolic products of microorganisms (bacteria, fungi) on the glass surface.
[0003] The reasons why dirt adheres to glass water cups include the following three points: First, the micropores on the surface of the glass will form a microscopic rough surface, and the dirt adheres to the rough surface and firmly combines with the glass surface; second, the glass surface energy is high and has no non-stick effect. Dirt can easily adhere to the glass surface and is not easy to remove; third, glass is made of silicate material and has no antibacterial effect on the surface. The attachment of organic matter will cause the rapid reproduction of microorganisms. The metabolites of microorganisms contain corrosive and adhesive substances such as acids, enzymes, and pigments, which are easily and firmly deposited on the glass surface. Summary of the invention
[0004] The water cup provided in the present application forms a layer of transparent modified ceramic coating with added antibacterial material on the inner surface of the water cup, so that the water cup is not easy to scale during use, or the scale can be easily removed by flushing with water, wiping with cloth, etc.
[0005] To achieve the above objectives, this application specifically adopts the following technical solutions:
[0006] In a first aspect, the present application provides a method for preparing a water cup, the method comprising the following steps:
[0007] Adding an inorganic polysilazane material and a silane material into an alkaline aqueous solution, mixing them, and heating them to obtain a modified ceramic coating;
[0008] The modified ceramic coating is repeatedly applied to the inner surface of the glass cup body and sintered to form a modified ceramic coating.
[0009] In the above scheme, by forming a layer of transparent modified ceramic coating with added antibacterial material on the inner surface of the water cup, the water cup is not easy to scale during use, or the scale can be easily removed by flushing with water, wiping with cloth, etc.
[0010] In a feasible embodiment, the mass ratio of the inorganic polysilazane material to the silane material in the modified ceramic coating is 3:4 to 2:1.
[0011] In the above scheme, all the silane materials react, leaving a small amount of inorganic polysilazane to form a mixture of organic silazane and inorganic silazane, that is, a modified ceramic coating; when combined with a water cup, a small amount of inorganic silazane is hydrolyzed to form nano-silica that combines with the glass to fill the surface depressions, and the remaining modified polysilazane is cross-linked to form a film and tightly combined with the nano-silica, and a small amount of silicone oil generated by the polymerization of silane material monomers is filled in the modified polysilazane film layer, which together play a non-stick role.
[0012] In a possible embodiment, the silane material includes at least one of methyldichlorosilane and dimethyldichlorosilane.
[0013] In the above scheme, the silane material can convert the inorganic polysilazane material into an organic modified polysilazane material, so that the prepared modified ceramic coating has better non-stick and antibacterial effects.
[0014] In a feasible embodiment, the modified ceramic coating further comprises an antibacterial material accounting for 1% to 3% by weight.
[0015] In the above scheme, the antibacterial material can effectively resist bacteria during use, prevent the reproduction of bacteria and fungi, and avoid the generation of pollutants.
[0016] In a feasible embodiment, the antibacterial material is a nano-silver antibacterial agent.
[0017] In the above scheme, the nano silver antibacterial agent is a conventional antibacterial agent, which is easy to obtain and can reduce the preparation cost of the water cup.
[0018] In a feasible embodiment, the preparation method has at least one of the following features a to d:
[0019] a. The mixing method includes at least one of ultrasonic stirring and mechanical stirring;
[0020] b. The ultrasonic stirring frequency is 30KHz to 50KHz, and the ultrasonic stirring time is 5min to 10min;
[0021] c. The mechanical stirring rate is 800 rpm / min to 3000 rpm / min, and the mechanical stirring time is 20min to 60min;
[0022] d. The heating temperature is 60°C to 80°C, and the heating time is 1h to 3h.
[0023] In the above scheme, by controlling the parameters of the modified ceramic coating preparation process, the prepared modified ceramic coating has uniform slurry and good construction performance.
[0024] In a feasible embodiment, the preparation method has at least one of the following features a to c:
[0025] a. The coating method includes at least one of air spraying and immersion;
[0026] b. The sintering temperature is 180°C to 200°C;
[0027] c. The sintering time is 1h to 3h.
[0028] In the above scheme, by controlling the parameters of the modified ceramic coating preparation process, the prepared modified ceramic coating has good mechanical properties and can achieve better non-stick and antibacterial effects.
[0029] In a feasible embodiment, before repeatedly applying the modified ceramic coating to the inner surface of the glass body, the preparation method further comprises:
[0030] The glass body is pre-cleaned with an organic solvent, wherein the organic solvent includes at least one of ethanol, banana oil, acetone, isopropanol, and tetrahydrofuran.
[0031] In the above scheme, an organic solvent is used to clean the cup body, so that the modified ceramic coating has a stronger bonding force with the cup body and is not easy to fall off during use.
[0032] In a feasible embodiment, the water cup is made according to the above-mentioned preparation method, and the water cup includes a cup body, and the inner surface of the cup body is provided with a modified ceramic coating, and the modified ceramic coating includes a base layer formed on the inner surface of the cup body and a ceramic non-stick layer formed on the surface of the base layer away from the cup body; wherein the modified ceramic coating also includes an antibacterial material.
[0033] In the above scheme, by combining the inorganic polysilazane material with the silane material, the nano-silicon dioxide can be made into a substrate and firmly bonded to the glass surface, the ceramic non-stick layer is firmly bonded to the nano-silicon dioxide to form a non-stick surface, and the nano-silver antibacterial agent is dispersed therein to achieve an antibacterial effect.
[0034] In a feasible embodiment, the water cup has at least one of the following features a to d:
[0035] a. The substrate is a nano-silicon dioxide substrate;
[0036] b. The thickness of the base layer is 0.5 μm to 3 μm;
[0037] c. The thickness of the ceramic non-stick layer is 3 μm to 20 μm;
[0038] d. The antibacterial material is a nano-silver antibacterial agent.
[0039] In the above scheme, the base layer forms a firm bond with the micropores on the glass surface; on the other hand, the surface of the ceramic non-stick layer has excellent non-stick properties, which can effectively prevent the deposition of pollutants, scale, and tea stains. The coating formed by the combination of the two is dense and smooth, which can effectively prevent the penetration of pollutants, scale, and tea stains, thereby achieving the purpose of easy cleaning of the water cup; thirdly, the antibacterial material can effectively resist bacteria during use, prevent the reproduction of bacteria and fungi, and avoid the generation of pollutants.
[0040] Beneficial effects:
[0041] The water cup provided in the present application forms a layer of transparent modified ceramic coating with antibacterial material added on the inner surface of the water cup, so that the water cup is not easy to scale during use, or the scale can be easily removed by flushing with water, wiping with cloth, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 A schematic diagram of the cross-sectional structure of a water cup provided in an embodiment of the present application;
[0043] Reference numerals:
[0044] 10-Water cup;
[0045] 1- cup body;
[0046] 2-basal layer;
[0047] 3- Ceramic non-stick layer.
[0048] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0050] In the description of this specification, unless otherwise expressly specified and limited, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance; unless otherwise specified or explained, the term "plurality" refers to two or more; the terms "connected", "fixed" and the like should be understood in a broad sense, for example, "connected" can be a fixed connection or a detachable connection, or an integral connection, or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium.
[0051] For those skilled in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0052] In the description of this specification, it should be understood that the directional words such as "upper" and "lower" described in the embodiments of the present application are described at the angles shown in the accompanying drawings and should not be understood as limiting the embodiments of the present application. In addition, in the context, it should also be understood that when it is mentioned that an element is connected to another element "upper" or "lower", it can not only be directly connected to another element "upper" or "lower", but also indirectly connected to another element "upper" or "lower" through an intermediate element.
[0053] In a first aspect, the present application provides a method for preparing a water cup 10, the preparation method comprising the following steps:
[0054] Step S10, adding an inorganic polysilazane material and a silane material into tetrahydrofuran, mixing them, and heating them to obtain a modified ceramic coating;
[0055] Step S20, repeatedly coating the modified ceramic coating on the inner surface of the cup body 1, and sintering to form a modified ceramic coating.
[0056] In the above scheme, by forming a transparent modified ceramic coating with added antibacterial material on the inner surface of the water cup 10, the water cup 10 is not easy to scale during use, or the scale can be easily removed by flushing with water, wiping with cloth, etc.
[0057] In step S10, the atoms bound to the silicon element and the nitrogen element in the inorganic polysilazane material used are all hydrogen atoms. During the mixing process, some hydrogen atoms in the inorganic polysilazane material are replaced by the organic groups of the silane material to obtain an organic modified polysilazane material. The organic polysilazane material has the following advantages as a modified ceramic coating for preparing a modified ceramic coating: first, it is an excellent coating film-forming material, which can be used in different environments and has excellent properties such as high temperature resistance, excellent weather resistance and chemical corrosion resistance; second, the obtained modified ceramic coating has high hardness (9H+), ultraviolet transparency, corrosion resistance, heat resistance and thermal stability; third, the modified ceramic coating is tightly attached to the surface of the metal cup body, glass cup body and ceramic cup body.
[0058] The organic polysilazane material forms a modified ceramic coating on the surface of the cup body 1 that does not change the appearance color of the material and is waterproof and oil-proof, making the surface of the cup body 1 bright and easy to clean, and transforming post-dirt cleaning into pre-fouling protection. At the same time, stains cannot penetrate into the interior of the cup body 1, effectively preventing the cup body 1 from corrosion and aging, and effectively extending the service life of the cup body 1.
[0059] Specifically, the mass ratio of inorganic polysilazane material to silane material is 3:4 to 2:1. Optionally, the ratio of inorganic polysilazane material to silane material can be 3:4, 1:1, 5:4, 3:2, 7:4, 2:1, etc., which are not limited here. In the actual application process, all the silane materials are reacted, leaving a small amount of inorganic polysilazane to form a mixture of organic silazane and inorganic silazane, that is, a modified ceramic coating. When combined with a water cup, a small amount of inorganic silazane is hydrolyzed to form nano-silica that combines with the glass to fill the surface depressions, and the remaining modified polysilazane is cross-linked to form a film and tightly combined with the nano-silica. A small amount of silicone oil generated by polymerization of silane material monomers is filled in the modified polysilazane film layer, which together play a non-sticky role. The mass fraction of the inorganic polysilazane material in the solution is too large, and the hydrogen atoms on some of the inorganic polysilazane materials are not replaced during the preparation process. The modified ceramic coating is doped with inorganic polysilazane materials that have not participated in the reaction. The modified ceramic coating obtained after the modified ceramic coating is formed into a film has poor non-stick properties and cannot achieve the effect of non-stick and easy cleaning; the mass fraction of the inorganic polysilazane material in the solution is too small, and the modified ceramic coating prepared by the final reaction has good non-stick properties, but poor bonding with the water cup.
[0060] The silane material mixed with the inorganic polysilazane material includes at least one of methyldichlorosilane and dimethyldichlorosilane. The silane material is used in the mixing process. The methyl groups in the silane material can replace part of the hydrogen atoms in the inorganic polysilazane material, so that the inorganic polysilazane material is converted into an organic modified polysilazane material.
[0061] The mixing process is to mix and heat the alkaline aqueous solution with a pH value of 8 to 9 in an alkaline aqueous solution by means of ultrasonic stirring and mechanical stirring.
[0062] It should be noted that during mixing, antibacterial materials are also added to the alkaline aqueous solution, and the antibacterial materials are used to prevent the proliferation of bacteria and fungi. The mass proportion of the antibacterial material in the prepared modified ceramic coating is 1% to 3%. Optionally, the mass proportion of the antibacterial material in the modified ceramic coating can be 1%, 1.3%, 1.6%, 1.9%, 2.1%, 2.4%, 2.7%, 3%, etc., which are not limited here. If the mass proportion of the antibacterial material in the modified ceramic coating is too large, it will affect the film-forming properties of the coating and increase the preparation cost; if the mass proportion of the antibacterial material in the modified ceramic coating is too small, the antibacterial effect will be reduced, and the proliferation of bacteria and fungi cannot be prevented. Preferably, the mass proportion of the antibacterial material in the modified ceramic coating can be 1% to 5%.
[0063] Specifically, during the mixing process, when ultrasonic stirring is used, the ultrasonic frequency of ultrasonic stirring is 30KHz to 50KHz, and the time of ultrasonic stirring is 5min to 10min. Optionally, the ultrasonic frequency of ultrasonic stirring can be 30KHz, 34KHz, 38KHz, 42KHz, 46KHz, 50KHz, etc., and the time of ultrasonic stirring can be 5min, 6min, 7min, 8min, 9min, 10min, etc. Ultrasonic wave is a liquid as a medium, and high-frequency ultrasonic vibration is added to the liquid. Since ultrasound is a mechanical wave, it is not absorbed by molecules, and causes the vibration movement of molecules during the propagation process, thereby producing a dispersed stirring effect. The ultrasonic frequency and the time of ultrasonic stirring can be selected according to actual needs, and are not limited here.
[0064] When mechanical stirring is used, the rate of mechanical stirring is 800rpm / min to 3000rpm / min, and the time of mechanical stirring is 20min to 60min. Optionally, the rate of mechanical stirring can be 800rpm / min, 1200rpm / min, 1600rpm / min, 2000rpm / min, 2400rpm / min, 2800rpm / min, 3000rpm / min, etc., and the time of mechanical stirring can be 20min, 30min, 40min, 50min, 60min, etc. If the rate of mechanical stirring is too large or the stirring time is too long, bubbles will be generated during the stirring process, affecting the preparation effect; if the rate of mechanical stirring is too small or the stirring time is too short, the substances in the aqueous solution are not mixed evenly, and the prepared modified ceramic coating does not meet the required requirements. Preferably, the rate of mechanical stirring can be 1000rpm / min to 1500rpm / min, and the time of mechanical stirring can be 30min to 45min.
[0065] It should be noted that mechanical stirring and ultrasonic stirring can also be used simultaneously, and can be selected according to actual conditions, and are not limited here.
[0066] The stirred alkaline aqueous solution is heated at a temperature of 60°C to 80°C for a heating time of 1h to 3h. Optionally, the heating temperature may be 60°C, 64°C, 68°C, 72°C, 76°C, 80°C, etc., and the heating time may be 1h, 1.4h, 1.8h, 2.2h, 2.6h, 3h, etc. The mixed alkaline aqueous solution can be defoamed and heated to remove bubbles generated during the stirring process to prevent the bubbles from affecting the prepared modified ceramic coating. The heating temperature and heating time can be selected according to actual needs and are not limited here.
[0067] Before performing step S20, the preparation method also includes: using an organic solvent to pre-clean the cup body 1. In the present application, the organic solvent can use ethanol or a diluent to wipe the inner surface of the cup body 1 to remove impurities such as oil stains on the inner surface of the cup body 1, so that the modified ceramic coating has a stronger bonding force with the cup body 1 and is not easy to fall off during use.
[0068] In step S20, the modified ceramic coating is applied to the inner surface of the cup body 1 by air spraying and immersion to form a modified ceramic coating. Taking air spraying as an example, specifically, step S20 includes:
[0069] Step S21, preheating the cup body 1;
[0070] Step S22, spraying the modified ceramic coating on the surface of the preheated cup body 1 by air spraying process;
[0071] Step S23, after the modified ceramic coating is sprayed, the cup body 1 is sintered to obtain a modified ceramic coating.
[0072] In step S21, the preheating temperature of the cup body 1 is 40°C to 55°C. Optionally, the preheating temperature can be 40°C, 43°C, 46°C, 49°C, 52°C, 55°C, etc. Preheating the cup body 1 can activate the surface of the cup body 1, which is beneficial to the bonding of the modified ceramic coating. The preheating temperature can be controlled according to actual needs and is not limited here.
[0073] The preheated cup body 1 can be sprayed with the modified ceramic coating. In step S22, the air pressure of the spraying process is 0.25Mpa to 0.35Mpa. Optionally, the air pressure of the spraying process can be 0.25Mpa, 0.27Mpa, 0.29Mpa, 0.31Mpa, 0.33Mpa, 0.35Mpa, etc., which are not limited here. If the air pressure of the spraying process is too high, the atomization degree of the modified ceramic coating is too large, which makes the modified ceramic coating seriously dispersed and causes waste. If the air pressure of the spraying process is too low, the atomization degree of the modified ceramic coating is too low, the density of the prepared modified ceramic coating is not high, and the non-stick effect is low. Preferably, the air pressure of the spraying process can be 0.32Mpa.
[0074] It should be noted that the spraying process needs to be repeated until the target thickness is reached. After spraying, it is only necessary to wait for the previous spraying to dry at room temperature before the next spraying can be carried out.
[0075] During the spraying process of the modified ceramic coating, the organic polysilazane material in the atomized modified ceramic coating comes into contact with water vapor in the air, undergoes a hydrolysis reaction and is converted into nano-silicon dioxide and ceramic materials composed of silicon and oxygen. The nano-silicon dioxide has extremely strong permeability and can enter the micropores on the surface of the cup body 1 to form a nano-silicon dioxide base layer 2, which is firmly bonded to the cup body 1; the ceramic material forms a ceramic non-stick layer 3 attached to the surface of the nano-silicon dioxide base layer 2.
[0076] After the modified ceramic coating is sprayed, the cup body 1 is sintered. In step S23, the cup body 1 is sintered at a sintering temperature of 180°C to 200°C for 1h to 3h. Optionally, the sintering temperature can be 180°C, 185°C, 190°C, 195°C, 200°C, etc., and the sintering time can be 1h, 1.4h, 1.8h, 2.2h, 2.6h, 3h, etc. The sintering treatment can make the modified ceramic coating more tightly bonded to the cup body 1 and prevent the modified ceramic coating from falling off during use. The temperature and time of the sintering treatment can be selected according to actual needs, and are not limited here.
[0077] Through the above steps S10 and S20, a water cup 10 can be obtained which is not easy to scale during use, or the scale can be easily removed by flushing with water, wiping with cloth, etc.
[0078] In a second aspect, the present application provides a water cup 10, which is made according to the above-mentioned preparation method. Figure 1 This is a schematic diagram of the cross-sectional structure of a water cup 10 provided in an embodiment of the present application, as shown in FIG. Figure 1 As shown, the inner surface of the cup body 1 is provided with a modified ceramic coating, which includes a base layer 2 formed on the inner surface of the cup body 1 and a ceramic non-stick layer 3 formed on the surface of the base layer 2 away from the cup body 1; wherein the ceramic non-stick layer 3 includes an antibacterial material.
[0079] In the above scheme, by forming a transparent modified ceramic coating with added antibacterial material on the inner surface of the water cup 10, the water cup 10 is not easy to scale during use, or the scale can be easily removed by flushing with water, wiping with cloth, etc.
[0080] It should be noted that, in addition to the glass cup body 1, the modified ceramic coating of the present application can also be used on cup bodies 1 of other materials, such as at least one of stainless steel, titanium, glass, and ceramic. It can be understood that the stainless steel cup body 1 is strong and durable, and can prevent rust and corrosion; the titanium cup body 1 has an antibacterial effect; the ceramic cup body 1 does not contain harmful substances and is conducive to heat preservation. The material of the cup body 1 can be selected according to actual needs, and is not limited here.
[0081] The material of the base layer 2 that serves as a connection on the inner surface of the cup body 1 is nano-silicon dioxide. Nano-silicon dioxide particles are a kind of inorganic non-metallic material with a flocculent or mesh quasi-particle structure that is non-toxic, odorless, and pollution-free, with high strength and stability. There are a large number of unsaturated bonds and hydroxyl groups on the surface of nano-silicon dioxide, so a strong chemical adsorption film can make the base layer 2 firmly bonded to the inner surface of the cup body 1.
[0082] Specifically, the thickness of the nano-silica base layer 2 is 0.5μm to 3μm. Optionally, the thickness of the nano-silica base layer 2 can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, etc., which is not limited here. In actual application, the thickness of the pre-deposited nano-silica can be adjusted by controlling the reaction conditions, such as the surface drying temperature and time after spraying. If the thickness of the nano-silica base layer 2 is too thick, the preparation process is more difficult and the preparation cost is increased; if the thickness of the nano-silica base layer 2 is too thin, the bonding ability with the cup body 1 is reduced, and it is easy to fall off during use. Preferably, the thickness of the nano-silica base layer 2 can be 1μm to 2μm.
[0083] The thickness of the ceramic non-stick layer 3 arranged on the surface of the base layer 2 away from the cup body 1 is 3μm to 20μm. Optionally, the thickness of the ceramic non-stick layer 3 can be 3μm, 6μm, 9μm, 12μm, 15μm, 18μm, 20μm, etc., which is not limited here. If the thickness of the ceramic non-stick layer 3 is too thick, the preparation process is more difficult, the preparation cost is increased, and the coating quality is deteriorated, and pores, cracks and other phenomena are easily generated; if the thickness of the ceramic non-stick layer 3 is too thin, the non-stick ability of the ceramic non-stick layer 3 is reduced, and the deposition of pollutants, scale, and tea scale cannot be effectively prevented. It is easy to wear during use, resulting in non-stick failure and a short life. Preferably, the thickness of the ceramic non-stick layer 3 can be 10μm to 15μm.
[0084] The antibacterial property of the cup body 1 is achieved by adding antibacterial material to the ceramic non-stick layer 3. The antibacterial material used in this application is nano silver ion antibacterial material. Nano silver ion antibacterial material is a typical metal nano material with a very large specific surface area. The lack of adjacent atoms around it makes the silver ions have many unsaturated bonds. This structure provides many contact adsorption sites and reaction points for various reactions. It is easy to combine with foreign atoms through chemical bonds and has a strong ability to adsorb microorganisms.
[0085] In order to better demonstrate the antibacterial and easy-to-clean performance of the cooking utensils in the present application, relevant tests are now conducted on the cooking utensils in the present application. In the following tests, glass is prepared into cups with accommodating cavities of the same size.
[0086] Embodiment 1:
[0087] (1) preparing glass into a cup body with a receiving cavity and pre-treating and removing oil;
[0088] (2) Inorganic polysilazane material and methyldichlorosilane in a mass ratio of 3:4 were added to an alkaline aqueous solution for mixing, and then an antibacterial material was added, and mechanical stirring was first performed and then ultrasonic stirring was performed. The mechanical stirring rate was 2000 rpm / min, and the mechanical stirring time was 40 min. The ultrasonic frequency of the ultrasonic stirring was 3×10 4 Hz, and the stirring time is 7 minutes; the stirred mixed material is heated to 65°C and kept heated for 2 hours to obtain a modified ceramic coating, wherein the antibacterial material accounts for 1% by weight in the modified ceramic coating;
[0089] (3) The modified ceramic coating is sprayed onto the inner surface of the glass cup body by air spraying, and the surface is dried at 60°C for 5 minutes, and the above spraying and surface drying steps are repeated multiple times; sintering is performed at a sintering temperature of 190°C for 2 hours to form a modified ceramic coating with a thickness of 15 μm, wherein the thickness of the base layer is 2 μm, and the thickness of the ceramic non-stick layer is 13 μm.
[0090] Embodiment 2:
[0091] (1) preparing glass into a cup body with a receiving cavity and pre-treating and removing oil;
[0092] (2) Inorganic polysilazane material and methyldichlorosilane in a mass ratio of 5:4 were added to an alkaline aqueous solution for mixing, and then the antibacterial material was added, and mechanical stirring was first performed and then ultrasonic stirring was performed. The mechanical stirring rate was 2000 rpm / min, and the mechanical stirring time was 40 min. The ultrasonic frequency of the ultrasonic stirring was 3×10 4 Hz, the stirring time is 7 minutes; the stirred mixed material is heated to 65°C and kept heated for 2 hours to obtain a modified ceramic coating, wherein the antibacterial material accounts for 2% by weight in the modified ceramic coating;
[0093] (3) The modified ceramic coating is sprayed onto the inner surface of the glass cup body by air spraying, and the surface is dried at 60°C for 5 minutes, and the above spraying and surface drying steps are repeated multiple times; sintering is performed at a sintering temperature of 190°C for 2 hours to form a modified ceramic coating with a thickness of 15 μm, wherein the thickness of the base layer is 2 μm, and the thickness of the ceramic non-stick layer is 13 μm.
[0094] Embodiment 3:
[0095] (1) preparing glass into a cup body with a receiving cavity and pre-treating and removing oil;
[0096] (2) Inorganic polysilazane material and methyldichlorosilane in a mass ratio of 2:1 were added to an alkaline aqueous solution for mixing, and then an antibacterial material was added, and mechanical stirring was first performed and then ultrasonic stirring was performed. The mechanical stirring rate was 2000 rpm / min, and the mechanical stirring time was 40 min. The ultrasonic frequency of the ultrasonic stirring was 3×10 4 Hz, and the stirring time is 7 minutes; the stirred mixed material is heated to 65°C and kept heated for 2 hours to obtain a modified ceramic coating, wherein the antibacterial material accounts for 3% by weight in the modified ceramic coating;
[0097] (3) The modified ceramic coating is sprayed onto the inner surface of the glass cup body by air spraying, and the surface is dried at 60°C for 5 minutes, and the above spraying and surface drying steps are repeated multiple times; sintering is performed at a sintering temperature of 190°C for 2 hours to form a modified ceramic coating with a thickness of 15 μm, wherein the thickness of the base layer is 2 μm, and the thickness of the ceramic non-stick layer is 13 μm.
[0098] Embodiment 4:
[0099] (1) preparing glass into a cup body with a receiving cavity and pre-treating and removing oil;
[0100] (2) Inorganic polysilazane material and methyldichlorosilane in a mass ratio of 1:4 were added to an alkaline aqueous solution for mixing, and then an antibacterial material was added, and mechanical stirring was first performed and then ultrasonic stirring was performed. The mechanical stirring rate was 2000 rpm / min, and the mechanical stirring time was 40 min. The ultrasonic frequency of the ultrasonic stirring was 3×10 4 Hz, and the stirring time is 7 minutes; the stirred mixed material is heated to 65° C. and kept heated for 2 hours to obtain a modified ceramic coating, wherein the antibacterial material accounts for 0.5% by weight in the modified ceramic coating;
[0101] (3) The modified ceramic coating is sprayed onto the inner surface of the glass cup body by air spraying, and the surface is dried at 60°C for 5 minutes, and the above spraying and surface drying steps are repeated multiple times; sintering is performed at a sintering temperature of 190°C for 2 hours to form a modified ceramic coating with a thickness of 15 μm, wherein the thickness of the base layer is 2 μm, and the thickness of the ceramic non-stick layer is 13 μm.
[0102] Embodiment 5:
[0103] (1) preparing glass into a cup body with a receiving cavity and pre-treating and removing oil;
[0104] (2) Inorganic polysilazane material and methyldichlorosilane in a mass ratio of 3:1 were added to an alkaline aqueous solution for mixing, and then the antibacterial material was added, and mechanical stirring was first performed and then ultrasonic stirring was performed. The mechanical stirring rate was 2000 rpm / min, and the mechanical stirring time was 40 min. The ultrasonic frequency of the ultrasonic stirring was 3×10 4 Hz, and the stirring time is 7 minutes; the stirred mixed material is heated to 65°C and kept heated for 2 hours to obtain a modified ceramic coating, wherein the antibacterial material accounts for 4% by weight in the modified ceramic coating;
[0105] (3) The modified ceramic coating is sprayed onto the inner surface of the glass cup body by air spraying, and the surface is dried at 60°C for 5 minutes, and the above spraying and surface drying steps are repeated multiple times; sintering is performed at a sintering temperature of 190°C for 2 hours to form a modified ceramic coating with a thickness of 15 μm, wherein the thickness of the base layer is 2 μm, and the thickness of the ceramic non-stick layer is 13 μm.
[0106] Comparative Example 1:
[0107] (1) preparing glass into a cup body with a receiving cavity and pre-treating and removing oil;
[0108] (2) Inorganic polysilazane material and methyldichlorosilane in a mass ratio of 3:4 were added to an alkaline aqueous solution for mixing, and mechanical stirring was first performed and then ultrasonic stirring was performed, wherein the mechanical stirring rate was 2000 rpm / min, and the mechanical stirring time was 40 min; the ultrasonic stirring frequency was 3×10 4 Hz, stirring time is 7 minutes; heating the stirred mixed material to 65°C and keeping the heating time for 2 hours to obtain a ceramic coating;
[0109] (3) The ceramic coating is sprayed onto the inner surface of the glass cup body by air spraying, and the surface is dried at 60° C. for 5 minutes. The above spraying and surface drying steps are repeated multiple times; and the ceramic coating is sintered at a sintering temperature of 190° C. for 2 hours to form a ceramic coating with a thickness of 15 μm.
[0110] Comparative Example 2:
[0111] The glass is prepared into a cup body with a receiving cavity and is pre-treated to remove oil.
[0112] test
[0113] Antibacterial test: According to JISZ2801:2012, test and record the logarithmic value of antibacterial activity (required ≥2);
[0114] Easy-to-clean test: Pour 200 mL of fresh orange juice into a glass without a lid, place it in a constant temperature environment of 25°C for 24 hours, then rinse it with normal temperature tap water at a pressure of 0.2 MPa for 30 seconds, and observe whether the glass changes color. This is counted as one cycle. Repeat the above steps until contaminants are attached to the surface of the glass and it changes color.
[0115] Test Results
[0116] sample Staphylococcus aureus Escherichia coli Easy to clean test cycles Example 1 2.0 2.2 48 Example 2 2.8 2.5 180 Example 3 4.4 3.2 166 Example 4 0 0 After 2 cycles, the coating starts to fall off Example 5 4.6 4.5 The surface coating has slight cracks Comparative Example 1 0 0 15 Comparative Example 2 0 0 7
[0117] From the test results of Examples 1 to 5, it can be seen that when the mass ratio of the inorganic polysilazane material to the silane material is in the range of 3:4 to 2:1, the glass has a good non-stick effect and the coating is firmly bonded to the glass;
[0118] It can be seen from the test results of Examples 1 to 5 and Comparative Examples 1 to 2 that adding antibacterial materials to the modified ceramic coating enables the glass to have a good antibacterial effect.
Claims
1. A method for preparing a water cup, characterized in that: The preparation method comprises the following steps: Adding an inorganic polysilazane material and a silane material into an alkaline aqueous solution, mixing them, and heating them to obtain a modified ceramic coating; Repeatedly applying the modified ceramic coating to the inner surface of the glass cup body, and sintering to form a modified ceramic coating; The mass ratio of the inorganic polysilazane material to the silane material is 3:4 to 2:1; The modified ceramic coating also includes an antibacterial material accounting for 1% to 3% by weight.
2. The preparation method according to claim 1, characterized in that: The silane material includes at least one of methyldichlorosilane and dimethyldichlorosilane.
3. The preparation method according to claim 1, characterized in that: The antibacterial material is a nano silver antibacterial agent.
4. The preparation method according to claim 1, characterized in that: The preparation method has at least one of the following features a to d: a. The mixing method includes at least one of ultrasonic stirring and mechanical stirring; b. The ultrasonic stirring frequency is 30kHz to 50kHz, and the ultrasonic stirring time is 5min to 10min; c. The mechanical stirring rate is 800 rpm / min to 3000 rpm / min, and the mechanical stirring time is 20min to 60min; d. The heating temperature is 60°C to 80°C, and the heating time is 1h to 3h.
5. The preparation method according to claim 1, characterized in that: The preparation method has at least one of the following features a to c: a. The coating method includes at least one of air spraying and immersion; b. The sintering temperature is 180°C to 200°C; c. The sintering time is 1h to 3h.
6. The preparation method according to claim 1, characterized in that: Before repeatedly coating the modified ceramic coating on the inner surface of the glass body, the preparation method further comprises: The glass body is pre-cleaned with an organic solvent, wherein the organic solvent includes at least one of ethanol, banana oil, acetone, isopropanol, and tetrahydrofuran.
7. A water cup, characterized in that: The water cup is made according to the preparation method according to any one of claims 1 to 6, and the water cup includes a cup body, and a modified ceramic coating is provided on the inner surface of the cup body, and the modified ceramic coating includes a base layer formed on the inner surface of the cup body and a ceramic non-stick layer formed on the surface of the base layer away from the cup body; wherein the modified ceramic coating also includes an antibacterial material.
8. The water cup according to claim 7, characterized in that: The water cup has at least one of the following features a to d: a. The substrate is a nano-silicon dioxide substrate; b. The thickness of the base layer is 0.5 μm to 3 μm; c. The thickness of the ceramic non-stick layer is 3 μm to 20 μm; d. The antibacterial material is a nano-silver antibacterial agent.
Citation Information
Patent Citations
Modified ceramic coating, composite coating, preparation methods therefor, and cooking utensil
WO2024141891A2